The importance of fauna-mediated sediment O2 consumption in the NGOM hypoxic zone - Beck, Hannah; Maiti, Kanchan (Frontiers in Marine Science, 2025)
The northern Gulf of Mexico (NGOM) coastal shelf adjacent to the Mississippi and Atchafalaya rivers system experiences strong seasonal hypoxia in the late summer and coupled physical-biological models suggest that hypoxia formation in the NGOM is sensitive to benthic biogeochemical processes. However, the processes driving sediment oxygen consumption and their relationship to bottom oxygen concentration remain enigmatic. This study for the first time concurrently measured in situ total oxygen uptake (TOU) and diffusive oxygen uptake (DOU) during two different hypoxia seasons. The relatively large DOU: TOU ratio of 0.33 ± 0.07 observed during this study suggests more significant benthic infauna community activity driving oxygen fluxes than previously thought. Future hypoxia models for this region should consider the role of infaunal-mediated oxygen consumption in biogeochemical variables.